2006
DOI: 10.1128/jcm.00836-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Single-Nucleotide Polymorphism Genotyping System To Demonstrate the Unique Epidemiology of Methicillin-Resistant Staphylococcus aureus in Remote Aboriginal Communities

Abstract: Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) has emerged as a major public health problem in Australia, as in many other parts of the world. High rates of CA-MRSA skin and soft tissue infection have been reported from Aboriginal communities. We used a single-nucleotide polymorphism (SNP) genotyping typing system based on the multilocus sequence type (MLST) database to investigate the epidemiology of CA-MRSA and methicillin-sensitive S. aureus (MSSA) over a 12-month period in three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
130
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 43 publications
(54 reference statements)
10
130
2
1
Order By: Relevance
“…In general, impetigo presents as bullous or papular lesions that progress to crusted lesions, without accompanying systemic symptoms, on exposed areas of the body (usually the face or extremities). Recent studies of impetiginous lesions found recovery rates of 29 to 90% and 57 to 81% for Streptococcus pyogenes and S. aureus, respectively (313)(314)(315)(316).…”
Section: For Photos Of Classical S Aureus Sstis)mentioning
confidence: 99%
“…In general, impetigo presents as bullous or papular lesions that progress to crusted lesions, without accompanying systemic symptoms, on exposed areas of the body (usually the face or extremities). Recent studies of impetiginous lesions found recovery rates of 29 to 90% and 57 to 81% for Streptococcus pyogenes and S. aureus, respectively (313)(314)(315)(316).…”
Section: For Photos Of Classical S Aureus Sstis)mentioning
confidence: 99%
“…They accounted for 23% of all isolates and 70% of MRSA isolates recovered during a community study of impetigo (16), and clinical isolates were associated with a variety of disease states (22). Similar to other incidents of community-acquired MRSA, the majority of SCCmec cassettes found in CC75 were type IV (16).…”
mentioning
confidence: 92%
“…Surveillance of staphylococcal carriage and disease in the tropical northern region of the Northern Territory of Australia yielded methicillin-susceptible and methicillin-resistant Staphylococcus isolates that are highly divergent from S. aureus at the MLST loci and are therefore difficult to classify. These isolates were shown to be closely related to each other and were designated clonal complex 75 (CC75) (16). They accounted for 23% of all isolates and 70% of MRSA isolates recovered during a community study of impetigo (16), and clinical isolates were associated with a variety of disease states (22).…”
mentioning
confidence: 99%
“…The comparison of single-nucleotide polymorphisms (SNP) is also a sequence-based typing method [20] and provides the basis for real-time PCR or low-density arraybased methods [21]. SNP analysis of three Staphylococcus enterotoxin genes (set2, set5, and set7) was reported to have even higher discriminatory power than MLST [22].…”
Section: Past and Present Methods Of Dna-based Mrsa Typingmentioning
confidence: 99%